2021
DOI: 10.1057/s41262-020-00229-z
|View full text |Cite
|
Sign up to set email alerts
|

It’s all about the brand: place brand credibility, place attachment, and consumer loyalty

Abstract: Despite the growing attention brand credibility attracts in recent marketing literature, little is known about the credibility of place brands and their relationship with consumers’ loyalty. The present study builds on brand signalling and attachment theory to investigate whether credible place brands affect consumers’ attachment formation, their subsequent word of mouth (WOM) and intention to return. Survey data from an Alpine winter sport destination reveal that place brand credibility is a key antecedent of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(43 citation statements)
references
References 73 publications
1
41
1
Order By: Relevance
“…Loyalty was much less for BO Potentials, and there were often barriers for those people to attend. Considering that brand attachment and love is an antecedent of loyalty (Fernandes & Inverneiro, 2020; Park et al., 2010; Reitsamer & Brunner‐Sperdin, 2021; Shetty & Fitzsimmons, 2021), it would be appropriate that BO, again develop greater engagement, attachment and love with consumers, by enhancing experience at the opera. Developing a loyalty program with discounts and rewards could assist with enhancing customer relationships (Petersen et al., 2019), but also in developing loyalty to a brand (Koo et al., 2020).…”
Section: Discussion: Resonance At the Operamentioning
confidence: 99%
See 1 more Smart Citation
“…Loyalty was much less for BO Potentials, and there were often barriers for those people to attend. Considering that brand attachment and love is an antecedent of loyalty (Fernandes & Inverneiro, 2020; Park et al., 2010; Reitsamer & Brunner‐Sperdin, 2021; Shetty & Fitzsimmons, 2021), it would be appropriate that BO, again develop greater engagement, attachment and love with consumers, by enhancing experience at the opera. Developing a loyalty program with discounts and rewards could assist with enhancing customer relationships (Petersen et al., 2019), but also in developing loyalty to a brand (Koo et al., 2020).…”
Section: Discussion: Resonance At the Operamentioning
confidence: 99%
“…Brand attachment leads to consumption behaviour and higher levels of consumer loyalty (Park et al., 2010). Previous research reveals that a credible brand is an antecedent of brand attachment (Reitsamer & Brunner‐Sperdin, 2021), which influences brand loyalty. People who are attached to a brand will have a high intention to return, and brand attachment has a strong mediating effect.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Future researchers can test this model for other cities with different characteristics, for example, by comparing attractive vs nonattractive cities and their neighbourhoods (Lewicka, 2010b). Future research can also investigate the consequences of city brand love which may include city citizenship behaviour (Taecharungroj, 2016) and word-of-mouth (Reitsamer and Brunner-Sperdin, 2021). Prior research has also reported differences amongst natives and non-natives of a place in terms of length of residences (Hern andez et al, 2007).…”
Section: Conclusion and Future Research Directionmentioning
confidence: 99%
“…As seen from the above discussion, local attachment is the cognitive, emotional, and functional connection between consumers and a place, and when local attachment is combined with behavior, emotion will affect the behavior of individuals [ 85 ]. However, the degree of local attachment is affected by contextual preferences.…”
Section: Literature Reviewmentioning
confidence: 99%